An Eco-Feminist Water Revival Project in Gujarat. Issue 1 (June 2018) - Chakraborty, Meghadeepa
This article brings forth the strength of women in the revival, restoration and protection of the environment through collective efforts and initiatives. A small village of Gujarat is the case study. A group of women took the leadership and worked day and night to resolve the issue of water crisis in their village and trained themselves as barefoot geologists and revived the traditional water reservoir. The availability and accessibility of sufficient water has changed the entire struggle chain of the community and brought new life in the way of development.